The role of parents, schools and society in developing civil society in Senior High School - Efraim Semuel Nalle; Andy Nabu Sogen; Lenny Magdalena Tamunu (Faculty of Social and Political Science, Universitas Airlangga, 2018)
A qualitative research study using the phenomenology and cultural method was conducted in SMA Negeri 4, in Kupang. The data collection techniques were observation, interviews, and documentation. The data was obtained from the informants, and then processed and analysed by using interactive model analysis. The results of this study are 1) the lack of an optimal role from parents in building Civil Society; 2) schools embed the concept of society in their students but need to strengthen the students’ character; 3) the Civil Society concept in social life is not implemented properly, and 4) there are some obstacles which result in the absence of good civil society, such as the lack of character education, community high dependency on the government, a lack of facilities in relation to the children’s development at school, a lack of political education and political communication, and the practice of nepotism and interests in relation to social justice. The role of society in building a civil society community is still lacking. This is even though, in terms of tolerance and pluralism, parents and schools are already well implemented. However, the aspects of autonomy, democracy and social justice are not working properly, which turn out to be constraints when it comes to civil society formation.